Improving Precision in Navigating Laparoscopic Surgery Instruments toward a Planar Target Using Haptic and Visual Feedback - Howard, Thomas; Szewczyk, Jérôme (Frontiers in Robotics and AI, 2016)
The poor ergonomics of laparoscopic surgery are a widely recognized source of difficulty for surgeons, leading to sub-optimal surgeon performance and sometimes injury to the patient. The main causes for this are lost and distorted perception of interaction forces and instrument position. The latter, due to losses in visual and kinaesthetic depth perception and modified hand-eye coordination, can prevent precise navigation of instruments towards surgical targets or away from sensitive anatomic structures. This situation prompts us to explore methods for efficiently assisting the surgeon during instrument navigation. Here, we present experiments aimed at providing insights into the effectiveness of haptic (tactile and kinaesthetic), visual and combined feedback in assisting the navigation of a laparoscopic instrument tip towards a surgical target. Subjects placed in front of a laparoscopic trainer were tasked with following various instrument tip trajectories within a target plane while minimizing both deviations and task execution times. Feedback on the level of deviation was provided alternately through visual on-screen cues, tactile cues provided by vibration motors and / or kinaesthetic cues provided by a haptic interface co-manipulating the surgical instrument. Evaluations of these forms of feedback over two series of experiments implicating a total of 35 subjects (34 non-surgeon novices, 1 surgeon intern with experience in laparoscopy) show positive impacts of providing such feedback on precision in instrument navigation. Visual, tactile and combined cues lead to increased precision in navigation (up to 25% increase in time spent on target, and 32% reduction in deviation amplitudes), but usually at the cost of reduced task execution speed. However, the use of kinaesthetic feedback through soft virtual fixtures provided in a co-manipulated robot-assisted surgery set-up both significantly improved precision (32% increase in time spent on target, and 70% reduction in deviation amplitudes) and task execution speed (30% reduction in task completion times). The combination of visual and tactile feedback was shown to be helpful in correcting larger deviations from the target. These preliminary results are promising for implementation of low-cost tactile or combined visual and tactile feedback in applications to conventional laparoscopic instrument navigation, as well as to robot-assisted laparoscopic surgery.